Modified naphthol resin, preparation method thereof and resin composition containing modified naphthol resin
By salting and chemical grafting reaction of naphthol resin, the modified naphthol resin is formed, which solves the problems of high reactivity and poor processability of existing substrate materials, and achieves high glass transfer temperature, low thermal expansion coefficient and good heat resistance , suitable for the dielectric properties of modern electronic parts.
Patent Information
- Application Number
- CN202310966461.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-06-29
- Filing Date
- 2023-08-02
- Publication Date
- 2024-12-31
AI Technical Summary
Existing substrate materials such as polyphenylene ether resins and cyanate resins have high reactivity, poor processability, and dielectric properties and heat resistance to meet the challenges of modern electronic parts for high frequency and low delay requirements.
By salting and chemical grafting reaction of naphthol resin, a modified naphthol resin with terminal alkenyl groups is formed, which increases the glass transfer temperature, reduces the thermal expansion coefficient, increases the peel strength, and reduces the dielectric constant and dielectric loss.
The good application of modified naphthol resin in electronic components is achieved, the glass conversion temperature is improved, the thermal expansion coefficient and water absorption is reduced, and the heat resistance and dielectric characteristics are improved.
Smart Images

Figure CN119219872A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a resin and a preparation method thereof, in particular to a modified naphthol resin and a preparation method thereof. Background Art
[0002] With technological advancements, electronic components are being developed toward the goals of being lighter, thinner, shorter, and smaller. Furthermore, the advent of fifth-generation mobile networks (5G) has led to increasing industry demand for higher transmission frequencies, higher signal speeds, and lower latency. Consequently, the relevant fields are currently focused on developing substrate materials with high glass transition temperatures (Tg), low dielectric constants (Dk), low dissipation factors (Df), and excellent heat resistance to meet the dielectric properties (low dielectric constant, low dissipation factor) and heat resistance requirements of electronic substrates.
[0003] Common substrate materials such as polyphenylene ether resin and cyanate ester resin have good dielectric properties, but they are highly reactive, have a fast reaction rate, and have a gel point that is difficult to determine, resulting in poor processability. Summary of the Invention
[0004] The present invention relates to a modified naphthol resin and a preparation method thereof, as well as a resin composition containing the modified naphthol resin.
[0005] According to an embodiment of the present invention, a method for preparing a modified naphthol resin comprises the following steps: salting the naphthol resin and subjecting it to a chemical grafting reaction to form a modified naphthol resin having a terminal olefinic group in its structure. The reagent used in the chemical grafting reaction has a terminal olefinic group.
[0006] According to an embodiment of the present invention, the modified naphthol resin has a structure as represented by [Formula 3] in the specification.
[0007] According to an embodiment of the present invention, the resin composition includes the aforementioned modified naphthol resin.
[0008] According to an embodiment of the present invention, an electronic component includes a film layer formed by the aforementioned resin composition.
[0009] Based on the above, the application of modified naphthol resin can achieve better results in terms of increasing glass transition temperature, decreasing thermal expansion coefficient, increasing peel strength, decreasing water absorption and / or decreasing Dk / Df. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Figure 1 The present invention is a schematic flow chart of a method for preparing a modified naphthol resin according to an embodiment of the present invention.
[0011] Description of Reference Numerals
[0012] S10, S20: steps. DETAILED DESCRIPTION
[0013] In the following detailed description, for purposes of illustration and not limitation, exemplary embodiments disclosing specific details are set forth to provide a thorough understanding of the various principles of the present invention. However, it will be apparent to one of ordinary skill in the art, with the benefit of this disclosure, that the present invention may be practiced in other embodiments that depart from the specific details disclosed herein. Furthermore, descriptions of well-known devices, methods, and materials may be omitted so as not to obscure the description of the various principles of the present invention.
[0014] Ranges may be expressed herein as from "about" one particular value to "about" another particular value, which may also be expressed directly as one particular value and / or to another particular value. When expressing a range, another embodiment includes from the one particular value and / or to the other particular value. Similarly, when a value is expressed as an approximation by using the antecedent "about," it will be understood that the particular value forms another embodiment. It will be further understood that the endpoints of each range may be expressed in relation to or independent of the other endpoint.
[0015] In this document, non-limiting terms (such as may, can, for example, or other similar terms) mean that implementation, inclusion, addition, or presence is not necessary or optional.
[0016] Unless otherwise defined, all terms used herein (including technical and scientific terms) have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs. It will also be understood that terms (such as those defined in commonly used dictionaries) should be interpreted as having a meaning consistent with their meaning in the relevant technical context and should not be interpreted in an idealized or overly formal sense unless explicitly defined as such herein.
[0017] Please refer to Figure 1 The preparation method of the modified naphthol resin may include the following steps: Step S10: providing an unmodified naphthol resin; Step S20: subjecting the unmodified naphthol resin to salification and chemical grafting reaction to form a modified naphthol resin.
[0018] <Unmodified Naphthol Resin>
[0019] In one embodiment, the unmodified naphthol resin may be The above naphthol group may include 1-naphthol group. or 2-naphthol
[0020] In one embodiment, the unmodified naphthol resin does not have any nitro, nitroso or amine groups on the corresponding naphthol groups. In one embodiment, the unmodified naphthol resin does not have any nitro, nitroso or amine groups.
[0021] In one embodiment, the chemical formula of the unmodified naphthol resin may be as shown in the following [Formula 1].
[0022] [Formula 1]
[0023]
[0024] In [Formula 1], n can be a positive integer ranging from 2 to 40.
[0025] In one embodiment, the chemical formula of the unmodified naphthol resin can be similar to [Formula 1]. For example, the hydrogen atoms attached to the carbon atoms can be replaced by alkyl groups with one to five carbon atoms (calculated as: C1-C5). For another example, the hydroxyl group in the naphthol group can be located at other substitution positions.
[0026] In one embodiment, the number-average molecular weight (Mn) or weight-average molecular weight (Mw) of the polymer can be measured by gel permeation chromatography (GPC).
[0027] In one embodiment, the number average molecular weight or weight average molecular weight is used for estimation, and the average value of n may be between 1 and 30.
[0028] In one embodiment, the unmodified naphthol resin may be a commercially available product (e.g., trade name (manufactured by Shanghai Hengfeng New Material Technology Co., Ltd.) or commercially available products.
[0029] <Saltification of Unmodified Naphthol Resin>
[0030] In one embodiment, the unmodified naphthol resin shown in [Formula 1] can be ionized at the terminal hydroxyl group in the naphthol group by a suitable reaction to be suitable for subsequent reactions (eg, chemical grafting reaction).
[0031] In one embodiment, the terminal hydroxyl groups in the naphthol groups can be ionized by using a suitable alkaline solution. Since the terminal hydroxyl groups in the naphthol groups are ionized by using a suitable alkaline solution and can become corresponding salts, this can also be called saltization.
[0032] In one embodiment, the alkali solution may include a solution containing alkali metal ions or alkaline earth metal ions; preferably, a solution containing alkali metal ions. Cations with a valence of +3 or greater may cause unwanted side reactions. For example, the alkali solution may include sodium hydroxide, potassium hydroxide, sodium bicarbonate, potassium bicarbonate, sodium carbonate, potassium carbonate, or a mixture thereof, dissolved in a suitable solvent (e.g., water or an alcohol-water mixture).
[0033] In one embodiment, the pH value of the alkaline solution and / or the molar number of hydroxyl ions therein can be appropriately adjusted according to the total molar number of hydroxyl groups in the naphthol resin.
[0034] In one embodiment, based on the composition of the original reactants, the ratio of the total molar number of hydroxyl groups in the naphthol resin to the molar number of hydroxide ions in the alkali solution can be approximately 1:200 to 1:500; preferably, approximately 1:250 to 1:400; and even more preferably, approximately 1:300 to 1:350. Too low a molar number or concentration of hydroxide ions may slow the reaction or reduce the yield. Too high a molar number or concentration of hydroxide ions may cause unwanted side reactions.
[0035] In one embodiment, the unmodified naphthol resin after salification may be as shown in the following [Formula 2].
[0036] [Formula 2]
[0037]
[0038] In [Formula 2], the definition of n is substantially the same as the definition of n in the corresponding [Formula 2]. The reason for "n being substantially the same" as described above or below is that in chemical reactions, unintentional, but unexpected and / or unavoidable side reactions may occur.
[0039] As shown in [Formula 2], compared with the unsalted unmodified naphthol resin, the terminal hydroxyl group of the naphthol group in the unmodified naphthol resin can be ionized.
[0040] In one embodiment, the salted unmodified naphthol resin may have higher water solubility and / or higher reactivity compared to the unsalted unmodified naphthol resin.
[0041] In one embodiment, an appropriate catalyst or a suitable amount of catalyst may be added during the ionization of the terminal hydroxyl groups in the naphthol groups. In one embodiment, the catalyst is, for example, a quaternary ammonium compound (QAC). For example, the catalyst may include tetrabutylammonium bromide (TBAB) or tetraethylammonium bromide (TEAB). Quaternary ammonium compounds can provide good interfacial activity for reactants and / or increase the phase transfer rate.
[0042] <Chemical Grafting Reaction>
[0043] For the unmodified naphthol resin after salification, its ionized terminal hydroxyl groups can be considered nucleophiles. Therefore, the unmodified naphthol resin after salification can be modified by grafting the ionized terminal hydroxyl groups through nucleophilic substitution.
[0044] The modified naphthol resin after the graft substitution can be represented by the following [Formula 3].
[0045] [Formula 3]
[0046]
[0047] In [Formula 3], the definition of n is substantially the same as the definition of n in the corresponding [Formula 1] and / or [Formula 2].
[0048] In [Formula 3], V may be a functional group having a terminal alkenyl group. In one embodiment, V may be a functional group having 2 to 3 carbon atoms and having a terminal alkenyl group. In one embodiment, V may be a vinyl group. ), allyl group ) or isopropenyl group In one embodiment, V may be a vinyl group or an isopropenyl group. In other words, the modified naphthol resin has a terminal alkenyl group.
[0049] In [Formula 3], L is a linking group having a double bond. In one embodiment, L can be a linking group having 1 to 11 carbon atoms and at least one double bond. In one embodiment, L can be a ketone group. ), phenylene group, which may be substituted with an alkyl group or not. ) or an alkyl-substituted or unsubstituted methylbenzyl group In one embodiment, L may be a keto group or a methylbenzyl group which may or may not be substituted with an alkyl group. In one embodiment, L may be a keto group or a methylbenzyl group. "Alkyl substitution" as described above or below may mean that at least one hydrogen is replaced by an alkyl group having one to five carbon atoms (calculated as: C1-C5).
[0050] In one embodiment, the electrophilic reagent used in the chemical grafting reaction is a monomer molecule having a terminal alkenyl group, and the monomer molecule may include a halide, an alkene halide, or an alkene anhydride.
[0051] In one embodiment, the monomer molecule may include halomethylstyrene. Taking 4-halomethylstyrene as an example, it may be shown in the following [Formula 4].
[0052] [Formula 4]
[0053]
[0054] In [Formula 4], X can be a fluoro group, a chloro group, a bromo group, or an iodo group. Preferably, X is chloro (i.e., chloromethylstyrene).
[0055] In one embodiment, the monomer molecule may include acrylic anhydride, which may be shown as the following [Formula 5].
[0056] [Formula 5]
[0057]
[0058] In one embodiment, the monomer molecule may include methacrylic anhydride, which may be shown as the following [Formula 6].
[0059] [Formula 6]
[0060]
[0061] In one embodiment, the monomer molecule may include methacryloyl chloride, which may be shown in the following [Formula 7].
[0062] [Formula 7]
[0063]
[0064] In one embodiment, taking the monomer molecule as 4-halomethylstyrene as an example, the modified naphthol resin can be shown as the following [Formula 8].
[0065] [Formula 8]
[0066]
[0067] In [Formula 8], the definition of n is substantially the same as the definition of n in the corresponding [Formula 1] and / or [Formula 2].
[0068] In one embodiment, taking the monomer molecule as methacrylic anhydride or methacrylic chloride as an example, the modified naphthol resin can be shown as the following [Formula 9].
[0069] [Formula 9]
[0070]
[0071] In [Formula 9], the definition of n is the same as the definition of n in the corresponding [Formula 1] and / or [Formula 2].
[0072] <Application of modified naphthol resin>
[0073] Since the modified naphthol resin represented by [Formula 8] or [Formula 9] can have lower dielectric properties, higher glass transition temperature (Tg), lower coefficient of thermal expansion (CTE) and / or better heat resistance, it can be suitable for application in electronic products.
[0074] Since the modified naphthol resin represented by [Formula 8] or [Formula 9] can be easily dissolved in common organic solvents (such as toluene or methyl ethyl ketone (MEK), it is relatively convenient to use.
[0075] In one embodiment, the modified naphthol resin represented by [Formula 8] or [Formula 9] may have better dielectric properties, heat resistance, flame retardancy, low moisture absorption and / or adhesion properties when used in electronic products.
[0076] In one embodiment, the resin composition may include the modified naphthol resin of the aforementioned embodiment. For example, the basic formula (ie, the total resin composition) of the resin composition includes at least the modified naphthol resin of the aforementioned embodiment.
[0077] In one embodiment, based on 100 parts by weight of the basic formula (ie, the total resin composition) of the resin composition, the modified naphthol resin may be 30 to 60 parts by weight; preferably, 40 to 50 parts by weight.
[0078] In one embodiment, the base formula of the resin composition may further include a bismaleimide resin. In one embodiment, based on 100 parts by weight of the base formula of the resin composition, the bismaleimide resin may be present in an amount of 10 to 30 parts by weight; preferably, 15 to 25 parts by weight.
[0079] In one embodiment, the basic formula of the resin composition may further include other polymers. In one embodiment, based on 100 parts by weight of the basic formula of the resin composition, the other polymers may be in an amount of 20 to 50 parts by weight; preferably, 30 to 40 parts by weight.
[0080] In one embodiment, the aforementioned other polymer is not a naphthol resin (whether or not modified). In one embodiment, the aforementioned other polymer does not have a naphthol group. In one embodiment, the aforementioned other polymer does not have a derivative functional group of a naphthol group (such as a salified, esterified or etherified naphthol group). In one embodiment, the aforementioned other polymer may include a styrene / butadiene copolymer (such as poly(styrene-butadiene-styrene) (Poly(styrene-butadiene-styrene), SBS)) or a derivative thereof. Styrene / butadiene copolymer or its derivatives may be commercially available (such as those manufactured by TSRC Corporation, LCY Chemical Corporation, and Nippon Soda Co., Ltd.) and are often referred to as synthetic rubber.
[0081] In one embodiment, the resin composition may further include an additive formulation. The additive formulation is substantially not a resin, polymer, or the like. The additive formulation may include, for example, a flame retardant, an inorganic filler, or a combination thereof.
[0082] In one embodiment, the addition of a flame retardant can enhance the flame resistance or flame retardancy of the resin composition. As used herein, "flame retardant" or "flame retardant" means that the object (e.g., film, layer, or structure) can pass a standard flame retardancy test. For example, the UL94 plastic flammability standard (Test for Flammability of Plastic Materials for Parts in Devices and Appliances) published by Underwriters Laboratories Inc. (UL) in the United States is at least HB grade.
[0083] In one embodiment, the flame retardant includes a bromine-based flame retardant, a phosphorus-based flame retardant, or a combination thereof.
[0084] In one embodiment, the addition of an inorganic filler can increase the viscosity of the resin composition. For example, the inorganic filler can be silicon dioxide, titanium dioxide, aluminum hydroxide, aluminum oxide, magnesium hydroxide, magnesium oxide, calcium carbonate, boron oxide, calcium oxide, strontium titanate, barium titanate, calcium titanate, magnesium titanate, boron nitride, aluminum nitride, silicon carbide, cerium dioxide, or a combination thereof.
[0085] In one embodiment, the silica used as the inorganic filler may include fused silica or crystalline silica. In one embodiment, considering the dielectric properties when applied to a copper foil substrate, fused silica is more preferred.
[0086] In one embodiment, the titanium dioxide used as the inorganic filler may include titanium dioxide with rutile, anatase, or brookite structures. In one embodiment, considering the dielectric properties when applied to a copper foil substrate, titanium dioxide with rutile structure is more preferred.
[0087] In one embodiment, based on 100 parts by weight of the basic formula of the resin composition, the flame retardant may be additionally added in an amount of 20 to 40 parts by weight, which may be calculated as 20 to 40 parts per hundred parts of resin; preferably, about 25 to 35 parts per hundred parts of resin.
[0088] In one embodiment, based on 100 parts by weight of the basic formula of the resin composition, the inorganic filler may be additionally added in an amount of 50 to 70 parts by weight, which may be calculated as 50 to 70 PHR; preferably, about 55 to 65 PHR.
[0089] In one embodiment, the resin composition can be used to manufacture electronic components (such as, but not limited to, copper foil substrates or printed circuit boards).
[0090] <Manufacturing of Copper Foil Substrates>
[0091] The modified naphthol resin of the aforementioned embodiment can be dissolved in a suitable solvent and mixed with other components to form a resin varnish, and a copper foil substrate can be prepared using conventional methods. For example, the resin composition of the aforementioned embodiment can be dissolved in a suitable solvent to form a resin varnish, which can be used to manufacture a copper foil substrate.
[0092] A method for manufacturing a copper foil substrate may be as follows.
[0093] 2116 fiberglass cloth is impregnated with the aforementioned resin varnish and then dried at approximately 170°C (impregnation machine temperature) for several minutes. The drying time is adjusted to achieve a prepreg melt viscosity of approximately 4,000 to 12,000 poise after drying. Four prepregs are then stacked between two approximately 35μm-thick copper foils and laminated (described below) to form a copper foil substrate in accordance with one embodiment.
[0094] The conditions / process of the pressing step are as follows:
[0095] Step 1: Raise the temperature from about 80°C to about 195°C at a rate of about 0.5 hours (recorded as: 85↗195°C, 0.5hr).
[0096] Step 2: Reduce the pressure from about 7 kg / cm2 to about 1 / 2 hour. 2 Increased to about 25kg / cm 2 (Can be recorded as: 7↗25kg / cm 2 , 0.5hr)
[0097] Step 3: At a temperature of about 195°C and a pressure of about 25 kg / cm 2 Press for about 2.0 hours (can be recorded as: 195℃ / 25kg / cm 2 , 2.0hr).
[0098] <Preparation Example of Modified Naphthol Resin>
[0099] The present invention will be described in detail below with reference to Examples and Comparative Examples, but the present invention is not limited to the following Examples at all.
[0100] <Example 1-1>
[0101] Take about 100 grams of commercially available unmodified naphthol resin (trade name Manufactured by Shanghai Hengfeng New Materials Technology Co., Ltd. and distributed by Suiye Industrial; including the unmodified naphthol resin shown in [Formula 1]), its hydroxyl value (or OH value, Hydroxyl value) is approximately 141. The aforementioned hydroxyl value can be calibrated using commonly used standards (such as, but not limited to, ISO 4629-2:2016, ASTM E222-10, GB / T 12008.3, and CNS 6681). Then, approximately 100 g of the aforementioned unmodified naphthol resin and approximately 113 g of 4-chloromethylstyrene are placed in a reaction vessel of appropriate capacity and diluted with an appropriate amount of toluene until the solid content accounts for approximately 30 wt% of the weight of the reactants (i.e., the aforementioned unmodified naphthol resin and chloromethylstyrene), wherein the amount of toluene used is approximately 498 g. In addition, approximately 1 gram of tetrabutylammonium bromide (which can serve as a catalyst) is added to the reaction vessel.
[0102] The reactants (ie, a toluene solution containing the unmodified naphthol resin and chloromethylstyrene, which are not necessarily completely dissolved, and containing tetrabutylammonium bromide catalyst) are stirred with a suitable stirring bar and heated to about 70°C.
[0103] After the aforementioned reactants were stirred and heated to about 70° C., about 68 g of a 50 wt % aqueous sodium hydroxide solution was continuously added dropwise over about 2 hours, with continuous stirring and a constant temperature (about 70° C.).
[0104] After the aforementioned dropwise addition is completed, stirring is continued at a constant temperature (about 70° C.) for about 4 hours.
[0105] After the reaction, the reaction mixture is poured into a methanol solution approximately five times its volume to precipitate the product. The precipitated product can be filtered. After washing several times with methanol and water, a modified naphthol resin as shown in [Formula 8] is obtained, designated A1 and referred to as modified resin A1.
[0106] <Example 1-2>
[0107] Prepared using the same or similar steps as in Example 1-1. The difference lies in adjusting the relative amounts of chloromethylstyrene and naphthol resin. Specifically, in Example 1-1, the molar amount of chloromethylstyrene is 1.05 times the total molar amount of hydroxyl groups in the naphthol resin (which can be expressed as an equivalent ratio of 1.05); in Example 1-2, the molar amount of chloromethylstyrene is 1.07 times the total molar amount of hydroxyl groups in the naphthol resin (which can be expressed as an equivalent ratio of 1.07).
[0108] The modified naphthol resin shown in [Formula 8] can be obtained by the method of <Example 1-2>, which is numbered A2 and can be referred to as: A2 modified resin.
[0109] A1 and A2 modified resins may be structurally similar, but differ in their chain length distributions due to differences in the corresponding equivalents used during preparation. This chain length distribution can be determined using the polydispersity index described below.
[0110] <Examples 1-3>
[0111] Take approximately 100 grams of the same unmodified naphthol resin used in <Example 1-1>. Then, add the aforementioned approximately 100 grams of unmodified naphthol resin to a reaction vessel of appropriate capacity and dilute it with an appropriate amount of toluene until it is at least completely dissolved, wherein the amount of toluene used is approximately 498 grams. In addition, add approximately 1 gram of tetrabutylammonium bromide (which can serve as a catalyst) to the reaction vessel. During the process of adding the aforementioned unmodified naphthol resin, toluene, and / or tetrabutylammonium bromide, stir with an appropriate stirring bar and heat to approximately 70°C.
[0112] After heating to about 70° C., about 68 g of a 50 wt % sodium hydroxide aqueous solution is directly added at a constant temperature (about 70° C.) and reacted for about 1 hour with continuous stirring to produce a salted naphthol resin as shown in [Formula 2].
[0113] Then, about 4.37 grams of methacrylic anhydride (eg, [Formula 6]), totaling about 68 grams, was added dropwise over about 1 hour, with continuous stirring and a constant temperature (about 70° C.).
[0114] After the aforementioned dropwise addition is completed, stirring is continued at a constant temperature (about 70° C.) for about 10 hours.
[0115] After the reaction, the reaction mixture is poured into a methanol solution approximately five times its volume to precipitate the product. The precipitated product can be filtered and then washed several times with methanol and water to obtain a modified naphthol resin as shown in [Formula 9], designated A3 and abbreviated as A3 modified resin.
[0116] <Examples 1-4>
[0117] Prepared using the same or similar procedures as in Example 1-3. The difference lies in adjusting the relative amounts of methacrylic anhydride and naphthol resin. Specifically, in Example 1-3, the molar amount of methacrylic anhydride was 1.05 times the total molar amount of hydroxyl groups in the naphthol resin (which can be expressed as an equivalent ratio of 1.05); in Example 1-4, the molar amount of methacrylic anhydride was 1.07 times the total molar amount of hydroxyl groups in the naphthol resin (which can be expressed as an equivalent ratio of 1.07).
[0118] The modified naphthol resin shown in [Formula 9] can be obtained by the method of <Example 1-4>, which is numbered A4 and can be referred to as: A4 modified resin.
[0119] A3 and A4 modified resins may be structurally similar, but differ in their chain length distributions due to differences in the corresponding equivalents used during preparation. This chain length distribution can be determined using the polydispersity index described below.
[0120] The obtained modified naphthol resin was evaluated by the following evaluation methods, and the results are shown in [Table 1].
[0121] [Table 1]
[0122]
[0123] <Evaluation method>
[0124] Hydroxyl group transformation efficiency: This can be determined by comparing the hydroxyl number of the reactants before the reaction with the hydroxyl number of the products after the reaction. For example, if the hydroxyl number of the reactants before the reaction is approximately 141 and the hydroxyl number of the products after the reaction is approximately 0.3, the hydroxyl group transformation efficiency is approximately 99.8% (equation: 1-0.3 / 141 ≈ 99.8%). A hydroxyl group transformation efficiency closer to 100% indicates that more hydroxyl groups have been converted.
[0125] Number average molecular weight (Mn): The prepared modified naphthol resin was dissolved in tetrahydrofuran (THF) to prepare a 1 wt% solution. The Mn was then measured by gel permeation chromatography (GPC).
[0126] Weight average molecular weight (Mw): The prepared modified naphthol resin was dissolved in tetrahydrofuran (THF) to prepare a 1 wt% solution. The weight average molecular weight of the solution was then measured by gel permeation chromatography (GPC).
[0127] Polydispersity Index (PDI): The polydispersity index (PDI) is calculated by dividing the measured weight-average molecular weight by the number-average molecular weight (i.e., Mw / Mn). A lower PDI indicates a more concentrated molecular weight distribution. Under conditions where the initial reactants, catalyst, and their respective amounts are the same or similar, a lower PDI likely indicates a lower likelihood of side reactions, resulting in a more concentrated molecular weight distribution. Therefore, a more neutral molecular weight distribution (i.e., a lower PDI) can indicate greater uniformity in functionality, morphology, and / or structure, and can be considered a more uniform reaction / synthesis. Furthermore, a more neutral molecular weight distribution (i.e., a lower PDI) also reduces the proportion of side reaction products (e.g., larger polymer molecules formed by repolymerization). Consequently, the product is more stable in subsequent processing or application, resulting in higher quality and yield.
[0128] Residual Monomers: The amount of unreacted chloromethylstyrene (Example 1-1 or Example 1-2) or unreacted methacrylic anhydride (Example 1-3 or Example 1-4) can be measured and estimated by appropriate quantitative methods (such as, but not limited to, titration analysis or spectral analysis) to estimate their residual ratios.
[0129] <Application Examples and Comparative Examples of Copper Foil Substrates>
[0130] The resin varnish composition was prepared by mixing the components in the formula ratios shown in [Table 2] and [Table 3], and a copper foil substrate was prepared by the above-mentioned method.
[0131] The formula compositions in <Comparative Example>, <Example 2-1>, <Example 2-2>, <Example 2-3>, <Example 2-4>, and <Example 2-5> include corresponding basic formulas and additive formulas. The corresponding weight percentages (wt%) of the components included in the basic formula can be shown in [Table 2] and [Table 3]. In addition, the components in the additive formula are additionally added based on the total weight of the basic formula. Taking <Comparative Example> as an example, if the weight of the basic formula is 100 parts by weight, the additive formula includes 30 parts by weight of a flame retardant and can be calculated as 30 PHR (Parts per hundred parts of resin); and 60 parts by weight of a flame retardant and can be calculated as 60 PHR.
[0132] In the comparative example, the polyphenylene ether resin used was commercially available Saudi Basic Industries Corporation (SABIC) MX-90 resin.
[0133] The BMI used in <Comparative Example>, <Example 2-1>, <Example 2-2>, <Example 2-3>, <Example 2-4>, and <Example 2-5> is the same, which can be a commercially available bismaleimide (BMI) resin sold by KI Chemical Industry Co., Ltd. of Japan under the trade name BMI-70 series.
[0134] The synthetic rubber used in <Comparative Example>, <Example 2-1>, <Example 2-2>, <Example 2-3>, <Example 2-4>, and <Example 2-5> is the same, which can be commercially available SBS rubber produced by Nippon Soda Co., Ltd.
[0135] The flame retardant used in <Comparative Example>, <Example 2-1>, <Example 2-2>, <Example 2-3>, <Example 2-4>, and <Example 2-5> is the same, which can include the commercially available flame retardant sold by Clariant AG under the trade name OP935 series.
[0136] The inorganic fillers used in <Comparative Example>, <Example 2-1>, <Example 2-2>, <Example 2-3>, <Example 2-4>, and <Example 2-5> are the same, and may include commercially available silica fillers sold by Sibelco under the trade name 525ARI series.
[0137] [Table 2]
[0138]
[0139] [Table 3]
[0140]
[0141]
[0142] <Evaluation method>
[0143] a. Glass transition temperature (Tg)
[0144] Similar to the above method, the glass transition temperature (Tg) of films made from the resin compositions of the above formulations was measured using a dynamic mechanical analyzer (DMA).
[0145] b. Coefficient of thermal expansion (CTE)
[0146] Similar to the above method, the coefficient of thermal expansion (CTE) of films made from the resin compositions of the above formulations was measured by thermomechanical analysis (TMA) at a heating rate of about 20° C. / min.
[0147] c. Peel strength
[0148] In a similar manner to the above, the peel strength of films prepared from the resin compositions of the above formulations was measured using a universal tensile tester according to IPC-TM-650, Method 2.4.8.
[0149] d. Water absorption
[0150] Place a 5cm x 5cm square test piece in an oven at approximately 105°C for an appropriate measurement period (e.g., approximately 2 hours). Then, place the test piece in an autoclave at approximately 2 atm x 120°C. After approximately 120 minutes, record the weight difference before and after autoclaving (divided by the initial weight of the test piece x 100%) to determine the water absorption rate.
[0151] e. Heat resistance
[0152] The test method involves immersing the pressure cooker-tested test piece in a 288±5°C soldering oven and observing the result. If there is no delamination, the heat resistance is recorded as "acceptable."
[0153] f. Dielectric constant (Dk)
[0154] Dielectric constant test: The test method involves drying a 5cm x 5cm square copper foil substrate specimen (with the copper foil removed) in an oven at approximately 105°C for approximately 2 hours. The thickness is then measured using a thickness gauge. The specimen is then clamped into an impedance analyzer (Agilent E4991A) and the dielectric constant (Dk) data is measured at three points and averaged.
[0155] g. Dielectric loss (dissipation factor, Df)
[0156] Dielectric loss (Dissipation factor) test method: The test method is to remove the ketone foil of the copper foil substrate, a square test piece approximately 5cm × 5cm, and bake it in an oven at approximately 105°C for approximately 2 hours. The thickness is measured with a thickness gauge. The test piece is then clamped into an impedance analyzer (Agilent E4991A). The dissipation factor (Df) data at three points is measured and averaged.
[0157] <Evaluation Results>
[0158] The experimental results in Tables 2 and 3 show that, in Examples 2-1 through 2-5, the use of the modified naphthol resin according to one embodiment of the present invention resulted in improved heat resistance, a lower coefficient of thermal expansion, and superior adhesion. Furthermore, the low moisture absorption requirements of typical copper clad laminates (CCLs) were met. Furthermore, Dk and Df also met the dielectric properties of typical CCLs (e.g., a very low loss rating of 0.0030 to 0.0065 for Df).
[0159] Furthermore, compared to conventional resins (eg, polyphenylene ether resins used in conventional copper foil substrate manufacturing), other properties are comparable to or within corresponding standard specifications.
[0160] [Practicality]
[0161] In addition, the modified naphthol resin of the aforementioned embodiment of the present invention can be directly or indirectly applied to copper foil substrates and can be further processed into other consumer, industrial or suitable electronic components or electronic products (such as circuit boards or copper foil substrates).
[0162] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the above embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a modified naphthol resin, characterized in that: include: The naphthol resin is subjected to salification and chemical grafting reaction to form a modified naphthol resin having a terminal olefin group in the structure. The reagent used in the chemical grafting reaction has a terminal olefin group.
2. The preparation method of modified naphthol resin according to claim 1, wherein The naphthol resin has a structure represented by the following [Formula 1]: In [Formula 1], n is a positive integer from 2 to 40.
3. The preparation method of modified naphthol resin according to claim 1, characterized in that, The electrophilic reagent in the chemical grafting reaction includes a halide, an alkene halide or an alkene anhydride.
4. The preparation method of modified naphthol resin according to claim 3, characterized in that, The electrophilic reagent comprises halomethylstyrene, acrylic anhydride, methacrylic anhydride or methacryloyl chloride.
5. A modified naphthol resin, characterized in that: It has a structure represented by the following [Formula 3]: In [Formula 3], V is vinyl, allyl or isopropenyl, L is a linking group having a double bond, and n is a positive integer ranging from 2 to 40.
6. The modified naphthol resin according to claim 5, characterized in that Wherein L is a keto group.
7. The modified naphthol resin according to claim 5, characterized in that Wherein L is an alkyl-substituted or unsubstituted methylbenzyl group.
8. The modified naphthol resin according to claim 5, characterized in that The modified naphthol resin is prepared by the method for preparing the modified naphthol resin according to claim 1.
9. A resin composition, characterized in that include: The modified naphthol resin according to claim 5.
10. An electronic component, characterized in that: include: A film layer formed from the resin composition according to claim 9.
